ZnO nanoparticles obtained by pulsed laser ablation and their composite with cotton fabric: Preparation and study of antibacterial activity - Svetlichnyi, Valerii A.; Shabalina, Anastasiia V.; Lapin, Ivan N.; Goncharova, Darya A.; Nemoykina, Anna L. (Applied surface science)
A simple deposition method was used to prepare a ZnO/cotton fabric composite from water and ethanol dispersions of ZnO nanoparticles obtained by the pulsed laser ablation method. The structure and composition of the nanoparticles from dispersions and as-prepared composites were studied using electron microscopy, X-ray diffraction, and spectroscopy. The nanoparticles and composite obtained exhibited antibacterial activity to three different pathogenic microorganisms - Escherichia coli, Staphylococcus aureus, and Bacillus subtilis. An attempt to understand a mechanism of bactericidal effect of ZnO nanoparticles was made. It was shown that zinc ions and hydrogen peroxide were not responsible for antibacterial activity of the particles and the composite, and surface properties of nanoparticles played an important role in antibacterial activity of zinc oxide. The proposed composite is a promising material for use as an antibacterial bandage. @ 2016 Elsevier B.V. All rights reserved.